Economic structure, trade, and regional integration in southern Africa - Mukherjee, Natasha; Robinson, Sherman (International Food Policy Research Institute, 1997)
After decades of political, economic, and social turmoil, the countries of Southern Africa are entering a new economic and political future. Minority rule in South Africa ended with the first democratic elections in April 1994, and other countries in the regions are adopting more representative forms of government as well. In addition, the Southern African countries are also seeking closer economic relations with the world economy, and with one another, under the Southern African Development Community (SADC). With the abolition of apartheid and the lifting of international economic sanctions, the SADC countries expect that South Africa's trade links with its neighbors will strengthen. Some believe South Africa can become the new engine of growth for the region.